Transforming pesantren educational management through religious moderation in the era of technological disruption - Ani Aryati; Mustofa Mustofa; Zulkipli Jemain; Nur Azizah; A Suradi (Indonesian Journal of Educational Management and Leadership, 2026)
Purpose − Technological disruption has posed both challenges and opportunities for Pesantren as Islamic educational institutions rooted in tradition. On the one hand, rapid digital transformation demands managerial adaptation and innovation; on the other hand, Pesantren bear a strategic responsibility to cultivate religious moderation amid the proliferation of exclusive and intolerant religious narratives in digital spaces. This study aims to analyze the transformation of Pesantren educational management based on religious moderation in response to technological disruption through the POAC management framework (planning, organizing, actuating, controlling) Method − Employing a qualitative approach with a case study design, data were collected through in-depth interviews, observations, and document analysis. Findings − The findings reveal that the transformation of Pesantren educational management occurs in a systematic and contextual manner. At the planning stage, religious moderation is integrated into the vision, mission, and strategic educational policies. At the actuating stage, Pesantren mobilize educational resources adaptively by combining traditional learning methods with selective and value-oriented use of digital technology. Meanwhile, at the controlling stage, evaluation is conducted holistically by assessing not only academic achievement but also the internalization of moderate religious attitudes and digital ethics among students. The novelty of this study lies in the development of an integrated Pesantren educational management model that embeds religious moderation across all POAC functions within the context of technological disruption. This study contributes to the advancement of Islamic educational management scholarship and offers a practical framework for managing Pesantren in an adaptive, moderate, and sustainable manner in the digital era.